Increased Fetal Plasma and Amniotic Fluid Erythropoietin Concentrations: Markers of Intrauterine Hypoxia - Teramo, Kari A. (S. Karger AG, 2009)
Tissue hypoxia is the major stimulus of erythropoietin (EPO) synthesis in fetuses and adults. Since EPO does not cross the placenta and is not stored, fetal plasma and amniotic fluid levels indicate EPO synthesis and elimination. Acutely, the rate and magnitude of the increase in plasma EPO levels correlate with the intensity of hypoxia. Amniotic fluid EPO levels correlate with cord plasma levels in normal and abnormal pregnancies, with fetal plasma EPO levels in humans averaging 2.6 times higher than the corresponding amniotic fluid EPO levels. Recent experimental and clinical studies demonstrate that EPO has neuroprotective effects related to its anti-apoptotic and vascular growth-promoting properties. Although under basal conditions the fetal kidneys are the main site of EPO production, during hypoxia recent experimental data indicate an important role of the placenta. Amniotic fluid EPO levels have been shown to increase exponentially during fetal hypoxia in preeclamptic, diabetic and Rh-immunized pregnancies, to correlate inversely with cord blood pH, pO(2) and base excess and to predict neonatal morbidities and NICU admission. As an indicator of chronic intrauterine hypoxia, fetal EPO measurements have increased our knowledge about the pathogenesis and importance of intrauterine growth restriction, macrosomia, diabetic pregnancy, prolonged pregnancy, meconium staining, fetal hemorrhage, fetal anemia, maternal smoking and alcohol consumption, abnormal fetal heart rate and abnormal Doppler flow patterns. While the clinical utility of fetal amniotic fluid and plasma EPO measurements in the management of high-risk pregnancies and their offspring is promising, adequately powered clinical trials are urgently needed.